Principles of tissue engineering - Lanza, Robert P.; Langer, Robert; Vacanti, Joseph (San Diego Academic Press, 2000)
This edition is intended to serve as a comprehensive text for the student at the graduate level or the reseach scintist/physician with a special interest in tissue engineering. It should also function as a reference text for reseachers in many discipline. It is intended to cover the history of tissue engineering and the basic principles involvel, as well as to provide a comprehensive summary of the advances in tissue engineering in recent years and the state of the art as it exists today.
Keywords: Y Đa khoa